Hubungan Daya Tarik Wisata dengan Keputusan Pengunjung ke Pantai Pasir Jambak Padang - Rahman, Aidil; Yuliana, Yuliana; Pasaribu, Pasaribu (Journal of Home Economics and Tourism, 2016)
This research is aimed to determine the relationship between tourist attraction with visitors' decision to Pasir Jambak Beach Padang. This research is a correlational study. The population of this research was the visitors who've been to Pasir Jambak Beach Padang. The sampling technique is non-probability sampling, using purposive sampling. The number of samples in this reserach amounted to 86 peoples. Data was collected using a questionnaire with a Likert scale that has been tested for validity and reliability. Furthermore, the data was analyzed through descriptive analysis and correlation using SPSS version 16. The results of this research indicate that the ratings of visitors of tourist attraction in Pasir Jambak Beach Padang placed in enough category 62%, and 38% of respondents placed in poor category. More then 86% of visitors decision to Pasir Jambak Beach Padang placed in enough category, and 14% are in poor category. The correlation coefficient between the tourist attraction with visitors decision to Pasir Jambak Beach Padang is 0.767 with a significance value of 0.000 that means there is a very strong correlation and a positive and significant between tourist attraction with visitors' decision to Pasir Jambak Beach Padang.Keywords: Tourist Attractions, Visitor Decision.